Introduction to Special issue on “The Sixth International Symposium on Information and Communication Technology –SoICT 2015 (Informatica, 2016)
Editors' Introduction to the Special Issue on the Sixth International  Symposium on Information and Communication Technology (SoICT 2015, Hue City, Vietnam)